Modified Medial Canthoplasty as a New Surgical Technique for Chronic Paralytic Lagophthalmos Cases in Facial Nerve Palsy Patients - Reungwilaisup, Wichai (Journal of Health Science of Thailand, 2018)
Chronic paralytic lagophthalmos could be seriously harmful and sight threatening. Surgery always plays important roles in management of such condition. But, until now, there is no any single surgical method that covers all of the requirements including efficacy, safety, easiness to perform, low cost and good aesthetic result. The main purpose of this retrospective descriptive study was to introduce a newly modified surgical technique of medial canthoplasty, which was safe, effective, easy to perform, cheap and cosmetically acceptable to the patients. It was found their visual acuities were improved siqnificantly (p < 0.05) after the surgeries.